Corrosion of Cr in molten salts with different fluoroacidity in the presence of CrF3. (June 2020) - Liu, Yiyang; Song, Yulong; Ai, Hua; Shen, Miao; Liu, Hongtao; Zhao, Sufang; Liu, Yancheng; Fei, Zejie; Fu, Xiaobin; Cheng, Jinhui
Highlights: The corrosion rate of Cr in molten FLiNaK-CrF3 and FLiBe-CrF3 was compared by SEM and EIS analysis. The different corrosion mechanisms of Cr in molten FLiNaK-CrF3 and FLiBe-CrF3 were revealed through in-situ absorption spectroscopy analysis. The stability of Cr (II) was largely related to fluoroacidity and responsible for the corrosion difference in molten FLiNaK and FLiBe. Abstract: The corrosion rate of Cr in molten FLiBe–CrF3 and FLiNaK–CrF3 was studied by electrochemical impedance spectroscopy and static immersion analysis. Corrosion in FLiNaK–CrF3 was greater than that in FLiBe–CrF3 . The Cr corrosion kinetics were studied by high-temperature in situ ultraviolet-visible spectroscopy at 600 °C. In molten FLiBe–CrF3, the corrosion product was Cr(II), whereas in FLiNaK–CrF3, Cr(II) will convert to Cr(III) through disproportionation. After the addition of LiF into FLiBe, the Cr(II) can be converted to Cr(III), which indicates that the stability of Cr(II) is largely related to fluoroacidity.